Analysis of medication compliance in elderly hypertension in the Benu-Benua community health center: A cross-sectional study - Sulasry, Sulasry; Zainuddin, Asnia; Fristiohady, Adryan (STIKes Al-Ma'arif Baturaja, 2025)
Background: Hypertension in the elderly increases the risk of stroke, heart disease, and kidney failure, while adherence to pharmacological therapy remains a major issue requiring attention. Objective: This study aimed to analyze factors associated with antihypertensive medication adherence among elderly patients in the working area of the BLUD UPTD Benu-Benua Community Health Center. Methods: A cross-sectional design was employed involving a total of 67 hypertensive elderly respondents, determined using the Slovin formula (margin of error 10%) from a total population of 207 elderly individuals and selected through random sampling. Data were collected from November to December 2024 using a structured questionnaire that had been tested for validity and reliability (α = 0.685–0.922). Data analysis was conducted bivariately using the Chi-Square test with continuity correction and multivariately using binary logistic regression. Results: The results showed that medication adherence was higher among elderly individuals with good knowledge (76.9%) compared to those with poor knowledge (29.3%; p = 0.000), positive attitude (80.6%) compared to negative attitude (19.4%; p = 0.000), good motivation (63.6%) compared to low motivation (32.4%; p = 0.020), good family support (61.0%) compared to poor support (26.9%; p = 0.014), and good health worker support (64.1%) compared to poor support (25.0%; p = 0.004). Multivariate analysis showed that only the attitude variable significantly influenced medication adherence (p = 0.009 < 0.05; OR = 7.881; 95% CI = 1.678–37.021). Elderly individuals with positive attitudes were 7.881 times more likely to adhere to medication compared to those with negative attitudes. Attitude was the most dominant factor influencing antihypertensive medication adherence. Conclusion: These findings highlight the importance of educational interventions and family support to improve treatment adherence among elderly individuals with hypertension.